A non-traditional variant nonlinear energy sink for vibration suppression and energy harvesting. (1st December 2022) - Jin, Youzuo; Liu, Kefu; Xiong, Liuyang; Tang, Lihua
Highlights: A non-traditional nonlinear energy sink (NES) is proposed for the purpose of vibration suppression and energy harvesting. A multi-objective optimization is conducted to examine the trade-off between vibration suppression and energy harvesting. The optimal performance of the proposed non-traditional NES is compared with that of an optimally tuned non-traditional TMD. An experimental study is conducted to validate the simulation results. Abstract: In this article, an apparatus is proposed for simultaneous vibration suppression and energy harvesting in a broad frequency band. Traditionally, both the spring and the damper of a vibration absorber are directly connected to a primary system. Alternatively, a non-traditional way is to place the damper of the vibration absorber between the absorber mass and the base. A nonlinear energy sink (NES) is a type of nonlinear vibration absorber with an essential nonlinearity. When a strong nonlinear oscillator with a small linear stiffness is weakly coupled to a primary system, it behaves similarly to the NES, which is termed "variant NES". In the proposed apparatus, a variant NES is arranged in the non-traditional way in which a cantilever beam is placed between a pair of continuous-contact blocks which force the beam to deflect nonlinearly. An electromagnetic energy harvester, which also acts as a damper in the non-traditional variant NES, is formed by attaching a pair of permanent magnets to the free end of the beam and fixing a pair of coils to the base. The transient performances of the developed apparatus are investigated in terms of vibration suppression and energy harvesting using numerical simulation and compared with those of an optimum non-traditional vibration absorber. The simulation results are validated by an experimental study. It is found that the proposed non-traditional variant NES exhibits typical NES characteristics such as 1:1 resonance, targeted energy transfer (TET), and an initial energy threshold. With the prerequisite of TET being established under high-level initial energy, the best trade-off between vibration suppression and energy harvesting is achieved when the NES's oscillation decays slowly under low electrical damping or quickly under high electrical damping.